2014
DOI: 10.1017/s2078633614000113
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic characterization of indigenous chicken ecotypes in the north Gondar zone, Ethiopia

Abstract: An exploratory field survey was conducted in north Gondar zone, Ethiopia to identify and characterize the local chicken ecotypes. Seven qualitative and twelve quantitative traits from 450 chickens were considered. Chicken ecotypes such as necked neck, Gasgie and Gugut from Quara, Alefa and Tache Armacheho districts were identified, respectively. Morphometric measurements indicated that the body weight and body length of necked neck and Gasgie ecotypes were significantly (p < 0.01) higher than Gugut ecotypes ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
8
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 2 publications
9
8
0
2
Order By: Relevance
“…In the current study, males (92%) and females (78.3%) had snakehead shape across all the study districts, which is in good agreement with the reports of [11,14,23]. The results of shank color in the present study indicated that male (61%) and female (32%) chickens possessed yellow shank, which was in line with the findings of [7,10] who reported that majority of chicken populations (52.5%) in southern and eastern parts of Ethiopia were characterized by yellow shank.…”
Section: Qualitative Morphometrical Traitssupporting
confidence: 91%
“…In the current study, males (92%) and females (78.3%) had snakehead shape across all the study districts, which is in good agreement with the reports of [11,14,23]. The results of shank color in the present study indicated that male (61%) and female (32%) chickens possessed yellow shank, which was in line with the findings of [7,10] who reported that majority of chicken populations (52.5%) in southern and eastern parts of Ethiopia were characterized by yellow shank.…”
Section: Qualitative Morphometrical Traitssupporting
confidence: 91%
“…The IC populations in Rwanda had a similar level of diversity as their Ethiopian [45], Egyptian [38] and Cameroonian [8] counterparts, but had lower and higher diversity than those observed in southern China [19], European and Asian IC breeds [35], respectively. Among Rwanda IC, all populations showed a significantly high degree of inbreeding, which could have an impact on trait fixation in the populations.…”
Section: Plos Onementioning
confidence: 83%
“…Three types of duck breeds are reared in Thailand-namely, egg-laying ducks (Khaki Campbell), crossbreed of khaki Campbell and native laying ducks, and a small number of meat type ducks (Pekin, White Cherry Valley) (Gilbert et al, 2007). In Sudan and Ethiopia (Africa), large Beladi (LB), bare neck (BN), Betwil (BT) dwarf, naked neck, and Gasgie and Gugut breeds of chickens are kept in backyard farms (Getu et al, 2014;Wani et al, 2014).…”
Section: Species and Breeds Kept In Backyard Farmingmentioning
confidence: 99%